Design and analysis of the equipment for steel feeding into the intermediate ladle of a 6-strand continuous casting machine - Terekhov , D.A.; Stoyanov , O.M.; Galushkin , M.V.; Suslo , N.V.; Huk , E.S. (Theory and Practice of Metallurgy, 2024)
Taking into account the ever-increasing requirements for the performance characteristics of rolled products, the problem of improving the quality of billets produced by continuous casting technology is becoming increasingly important. The paper considers the technology of metal feeding of the steel pouring ladle (SPL) - open jet - intermediate ladle (IL) system of a continuous casting machine (CCM). The processes of metal flow in the presented system are shown. The design features of the elements of a long section CCM, which ensure the rational passage of the poured metal in the SRC - open jet - PC system, are indicated. This ensures the efficient formation of steel flows in the receiving chamber of the PC and creates conditions for improving the quality of the metal.